In search of Malay landscape design : characteristic and identification of traditional landscape at Sungai Perak / Mohd Khazli Aswad Khalid, Mohd Sabrizaa Abd Rashid and Ahmad Zamil Zakaria - Mohd Khazli Aswad, Khalid; Mohd Sabrizaa, Abd Rashid; Ahmad Zamil, Zakaria (2015)
Foreign landscape designs such as Balinese, Japanese and English style have a big influence on the local landscape design setting. Even after more than five decades of independence, most of the key and national level projects do not have a clear direction on the national landscape identity. Putrajaya itself for example, adopted foreign landscape design to develop the federal administrative centre of Malaysia. Furthermore, there is no understandable guideline in respect for national landscape identity or local characteristic by the Institute of Landscape Architects Malaysia (ILAM). Malay landscape design should become the main direction towards creating national identity. Moreover, Malay landscape design should be preserved as national heritage for future generations. This paper discusses an exploration that is undertaken to identify and establish the characteristics of Malay landscape design. The study includes observations on the characteristic and identity of Malay landscape design that is based on the functions and cultural community in Perak, at present. The objective of this study is to identify important elements and components in the establishment of Malay landscapes such as the types of vegetation and hardscapeat the old houses compound along Sungai Perak in Perak Tengah district. Eighteen (18) Kutai houses were selected as case study, using a quantitative method for the distribution of the components found in residential Malay house to determine the nature, function and overall similarity for each sample. At the end of the study, some characteristics could be obtained particularly Malay landscape to hardscape element and favorite vegetation that was found in the house compound. Result from this research can be used as a guide to design an appropriate Malay landscape which suits current lifestyle and also to introduce the identity of Malay landscape design